THE ROLE OF ACADEMIC SELF-EFFICACY IN IMPROVING THE ACHIEVEMENTS OF SAMBO ATHLETES IN KEDIRI REGENCY - Yayang Yayang; Puspodari Puspodari; Wing Prasetya Kurniawan (Journal of Physical Activity and Sports (JPAS), 2026)
An athlete’s performance is not only determined by physical ability and technique but is also influenced by psychological factors, one of which is academic self-efficacy. Student-athletes are expected to balance their academic and athletic activities, so they need strong self-confidence to cope with these various demands. This study aims to analyse the role of academic self efficacy in the performance of Sambo athletes in Kediri Regency, identify the factors that influence it, and describe its implementation in preparation for the 9th East Java Provincial Sports Week (PORPROV) in 2025. The study employs a qualitative approach with a descriptive design. The research informants consist of athletes, coaches, sports association officials, and athletes’ parents, who were selected through purposive sampling. Research data were collected through semi-structured interviews, observation, and documentation, and were then analysed using data reduction, data presentation, and conclusion drawing. The findings reveal that academic self-efficacy serves as a psychological stabilizer, where high efficacy levels directly correlate with improved time-management strategies and emotional resilience under competitive pressure. Furthermore, parental involvement and vicarious experiences through veteran athletes emerged as the primary external drivers for sustaining this efficacy during the high intensity preparation for the 2025 PORPROV. The development of academic self-efficacy is influenced by experiences of success, social support, vicarious experiences, and the ability to manage emotional states. Therefore, fostering academic self-efficacy should be an integral part of athlete development programs to support the achievement of optimal and sustainable performance.